PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN METODE PICTURE AND PICTURE PADA SISWA KELAS V SDN 1 SUKAMENANTI BANDAR LAMPUNG - Kusrina Kusrina (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The problem raised in this research is to improve the ability to write poetry of students with an integrated learning approach in learning Indonesian in class V SDN 1 Sukamenanti Kedaton Bandar Lampung Academic Year 2017 / 2018. This research was conducted because of the reality in the field that the ability to write class poetry V in SDN 1 Sukamenanti is classified as low, it is obtained that data in the basic competence of writing poetry the average value of students is 57.39 The average value obtained by these students in general has not reached the specified KKM, which is 65. Of the 28 students in SD Negeri 1 Sukamenanti Bandar Lampung only 10 or 36% of students achieved mastery. The rest, students can achieve completeness after taking remedial once, twice, or even up to three times. This shows that the ability to write poetry of fifth grade students at SD Negeri 1 Sukamenanti Bandar Lampung is low. For this reason, the most integrated learning approach is used in order to improve the ability to write poetry. To achieve the above research objectives, the authors use the "Classroom Action Research" research method abbreviated as CAR or class action research (CAR). Classroom action research (CAR) is action research carried out by teachers in the classroom. This model uses a spiral system of self-reflection that starts from plans, actions, observations, reflections, and re-planning which is the basis for a problem-solving design. And use an integrated approach in learning. Based on the results of the study it can be concluded that an increase in the ability to write poetry of students of SDN 1 Sukamenanti VB class after applying an integrated approach in learning Indonesian this can be seen in the initial conditions of the acquisition of an average value of 57.39 with the highest KM of 3.57%. In the first cycle the average value of 68.68 and the highest KM was 57.14%. In cycle II the average acquisition value is 71.93 and the highest KM is 64.29%, whereas the acquisition value in cycle III is an average of 77.04 and the highest KM in cycle III is 78.57%.